Improving the Photometric Accuracy of a CCD Television Camera - Bayramov, R.M.; Rahimov, A.T. (Herald of Azerbaijan Engineering Academy, 2024)
In thе paper, we consider improving the photometric accuracy of the tele-measuring system (TIS) by eliminating the influence of defects in the charge coupled device (CCD) matrix, by restoring the information lost due to this. One of the possible methods of increasing the photometric accuracy of a CCD television sensor may be the method of optical conversion in the optical path of a TV camera, i.e. when projecting an optical image onto the plane of a photoelectric converter. This particular method has been developed in this work.